Demographic and socioeconomic characteristics of agrarian households in the Dobrovce (Slovenia) and their impact on farming in the water protection zone - Horvat, Uroš (Journal for Geography, 2008)
The article discusses the main demographic and socioeconomic characteristics of agrarian households in the Dobrovce Settlement which is located in the proximity of Maribor, the second largest city in Slovenia. In this settlement is also one of Maribor’s important water supply stations. In accordance with the Water Protection Area Regulation, the use of fito-farmaceutical products in the water protection zone became prohibited in 2008. In the same year, they also put a break on the use of fertilizers containing nitrogen. However, after the transitional period, the use of these fertilizers is going to be banned completely. The new method of farming in the water protection zone is going to decrease the number of crops and influence the economic as well as social situation of the rural population in the settlement, as more than half of the land of agrarian households is situated in the protected zone.